(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In order to measure the friction force between woven fabric and skin at a wet condition, it was proposed that the completed wetting woven fabric could be hung on the line for different times to reach the different wet conditions. According to the water loss characteristic of woven fabric, the relative hanging time was used to describe the different wetting rates. The friction curves between 20 kinds of woven fabric and human skin were measured by the independently developed fabric-skin friction tester at 6 kinds of wet conditions. It was found that there were 4 kinds of friction-sliding displacement curves. They were normal friction curve, arched friction curve, rising friction curve and decline friction curve. According to the characteristic of various friction curves, 7 kinds of friction indices were defined to characterize the friction properties between woven fabric and skin at wet conditions. They were static friction, turning point between static friction and dynamic friction, average dynamic friction and its coefficient of mean deviation, maximum dynamic friction force, variation rate of dynamic friction and friction coefficient. Besides, it was also found that normal friction curve and rising friction curve usually occurred and their appearing probabilities were 44% and 47%, respectively.